Alcalá Somos Todos: A model of participation for children and youth - Armenteras Fuster, Carlos Francisco de; Cabra Díaz-Malaguilla, Mª del Mar; Gilabert Moncho, Mª Jesús; Marcelo Alonso, Laura; Valle López, Mª Dolores del (Pulso. Revista de educación, 2004)
Children and young people's involvement in our city is minimal and mostly connected to politics. This article recounts our experience with the "Alcalá Somos Todos" project, which was carried out in 2003 and aimed to provide children and youth with the opportunity to actively participate in the decision-making process of their city. During the municipal elections held on 25 May 2003, the Action Collective for Play and Education (CAJE) provided an opportunity for children to vote on proposals that interested them the most. These proposals were later going to be delivered to different political parties. The successful implementation of this project would not have been possible without the assistance of Juan Luengo, Director of CAJE, and Jacqueline Trillo, Activity Coordinator. We develop in detail all the steps that were taken in our project.